Extraction Flavonoid Compound from Foeniculum Vulgare and Study its Anti-Bacterial Activity - Mohanad Jawad Kadhim (Journal of Global Pharma Technology, 2018)
This investigation incorporated the extraction of the flavonoid compound in the fennel plant and the investigation of the natural viability of this compound by secluding it and playing out a few synthetic breaks down, to be specific the utilization of IR spectra, Uv spectroscopy, TLC, Using the shading information of the concentrate. Two distinct kinds of Staphylococcus aureus were watched. We watched the impact of flavonoids on the bacterial separates of positive and negative cumin individually (Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922). The adequacy of flavonoid extricate was observed to have the capacity to repress positive or negative bacteria. The zone of microbes’ hindrance19mm, 20mm.Keywords: Flavonoid, Antibacterial movement, Fennel plant, Foeniculum vulgare, phenolic compound, antimicrobial.